The Organization of the Funerary Cult in a Provincial Necropolis of the Old Kingdom: The Case of El-Hawawish - Sánchez Casado, Raúl (Antiguo Oriente, 2023)
This work approaches the organizational system of funerary cults in a provincial Old Kingdom necropolis, focusing on El-Hawawish as a case study. To accomplish our objective, first we look at the different operating models known from the study of other necropoli. These range from the most complex system, employing five phylai—used in the funerary temples of the kings and the tombs of the highest elite—to much simpler models that did not require hierarchical structures or a large number of staff. Given that we do not have texts of funerary provisions from El-Hawawish that provide us with direct information about the cults established there, we will use the analysis of the iconography of the tombs to try to understand what kind of operating patterns were in use and what type of officiants were employed. The results show us that some of the owners of the tombs of El-Hawawish implemented organized cults and complex hierarchical structures, and the members of the kin group of the deceased provided a significant amount of support by acting as cult performers.